Inhibition of anaerobic ammonium oxidation (anammox) bacteria by addition of high and low concentrations of chloramphenicol and comparison of attached- and suspended-growth. (January 2020) - Phanwilai, Supaporn; Piyavorasakul, Suratchana; Noophan, Pongsak (Lek); Daniels, Kevin D.; Snyder, Shane A.
Abstract: Inhibition of anammox activities was tested with two ranges of chloramphenicol (CAP) concentration (5, 10, 20, 50, and 100 mg L −1 ) and (100, 500, and 1000 μg L −1 ). In a short-term study, strong inhibition of activity was dependent of CAP concentration in both attached-growth (SBR-A) and suspended-growth (SBR-S) systems. The activities of attached-growth cultures at all CAP concentrations were reversible after 1 day, while activities for suspended-growth cultures were only gradually reversible dependent on the CAP concentrations. In long-term studies with daily additions of 6 mg L −1 CAP, the anammox activity on day 41 in SBR-A had decreased to 18% baseline (SAA reduced from 0.528 to 0.096 mg N mg −1 VSS d −1 ). More rapid reduction of anammox activity was observed in SBR-S, down to 17% baseline after only 27 days (SAA decreased from 0.576 to 0.096 mg N mg −1 VSS d −1 ). Inhibition was irreversible in both SBR-S and SBR-A after the long-term study. With lower CAP additions (100–1000 μg L −1 ), the activities in both reactors were stable during daily CAP addition for two weeks. Attached-growth cultures tended to be more tolerant of CAP addition than suspended-growth cultures. Both un-competitive and non-competitive models could be used to compare anammox activities with the higher CAP concentrations. The SAAmax [fx] (the maximum specific anammox activity) and h K i (the inhibition constant) of SBR-A were 0.48 mg N mg −1 VSS d −1 and 98.3 mg L −1, respectively. The SAAmax [fx] and K i of SBR-S were 1.25 mg N mg −1 VSS d −1 and 71.1 mg L −1, respectively. Highlights: Inhibition of anammox bacteria is directly proportional to chloramphenicol (CAP) concentrations. Inhibition of anammox bacteria by CAP is more pronounced in suspended-growth systems than in attached-growth systems. CAP -inhibited anammox systems are more likely to recover completely following short-term than after long-term exposure. Very little anammox inhibition is caused within two weeks under CAP concentrations between 100–1000 µg L −1 . A non-competitive or un-competitive Monod model may be used to predict anammox activity with higher CAP concentrations.